Energiewende and its impact on the German Automotive Industry - Tsap, Valeriia; Sankot, Ondřej, 1988-; Pantea, Smaranda; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The master thesis deals with the impact of the Energiewende on the German automotive industry, focusing on employment, industry revenues, and competitiveness. The primary aim of this thesis is to evaluate how the Energiewende has influenced the economic dimensions of the automotive industry over the last decade (2013–2023). A combination of statistical methods, contextual analysis, and expert studies was employed to assess the policy's impact on employment, industry revenues, and market competitiveness. Additionally, the thesis examines the progress of Energiewende targets, mapping their fulfillment to provide a comprehensive understanding of the policy's effectiveness.
Vedoucí práce: Ondřej Sankot
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses